Incidence and correction of vision impairment among elderly population in southern urban China. (18th November 2018) - Han, Xiaotong; Liao, Chimei; Liu, Chi; Lee, Pei Ying; Zhang, Jian; Keel, Stuart; He, Mingguang
Abstract : Importance: Data on the incidence of presenting vision impairment (PVI) and spectacle coverage rate (SCR) in urban China is limited. Background: To estimate the 6‐year incidence and risk factors for PVI and the SCR in urban Southern China. Design: Population‐based cohort study. Participants: A total of 1817 participants aged ≥35 years were identified from Guangzhou in 2008 at baseline and 1427 attended follow‐up examination in 2014. Methods: Presenting visual acuity (PVA) was measured using the ETDRS chart with habitual spectacles. Participants with PVA ≤20/40 underwent subjective refraction at the follow‐up visit. Incidence of PVI was calculated using the WHO and US criteria, respectively. The met‐need SCR was defined as the percentage of participants with PVA <20/40 that had been improved to ≥20/40 after correction. Main Outcome Measures: Incidence of PVI and SCR. Results: Incidence of PVI was 8.3% (95%CI, 6.9‐9.8) and 12.2% (95%CI, 10.5‐14.0) based on the WHO and US definition, respectively. Older age, female, lower education level, more myopic spherical equivalent and worse PVA at baseline were significantly related to a higher PVI incidence based on the WHO criteria, with similar associations identified using the US criteria except for gender. The overall met‐need SCR was 42.5%, and was lower among the elderly, more hyperopic participants or participants with lower education level. Conclusions and Relevance: The incidence of PVI is high in urban Southern China and spectacle wearing is available in less than half of those in need. This highlights the needs to promote spectacle coverage even in the urban population.